2019
DOI: 10.1109/access.2019.2937350
|View full text |Cite
|
Sign up to set email alerts
|

Extension of HMM-Based ADL Recognition With Markov Chains of Activities and Activity Transition Cost

Abstract: Ambient assisted living in smart home environments is becoming an important goal in an aging society with challenges in elderly care. A key component in such environments is the accurate recognition of activities of daily living from various sensor data. Recent research directions explored several classification methods, including hidden Markov models. This research presents a hidden Markov model-based system for activity recognition, and extends it with a second-order Markov chain model of activity sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Based on this, Donaj and Maučec (2019) presented a system for activity recognition and used a dataset from the CASAS to test and evaluate the proposed model. The core of these studies is to accurately grasp the daily living and activities of older adults from various sensor data [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on this, Donaj and Maučec (2019) presented a system for activity recognition and used a dataset from the CASAS to test and evaluate the proposed model. The core of these studies is to accurately grasp the daily living and activities of older adults from various sensor data [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gregor et al [ 24 ] used sensor data to recognize elderly people activity recognition. The dataset for this project was collected from several sensors including 51 motion sensors, 4 item sensors on selected items, 15 door sensors, and 5 temperature sensors installed in different rooms of the apartment.…”
Section: Related Workmentioning
confidence: 99%
“…Data-driven approaches use various machine learning techniques to learn activities from collected sensor data. The most frequently used are: Naive Bayes classifier [ 15 ], Hidden Markov Models [ 8 , 16 , 17 ], Support Vector Machines [ 3 ], dictionaries of patterns [ 18 ], and neural networks [ 6 , 19 , 20 ]. These approaches require a great amount of annotated data to train the models accurately.…”
Section: Related Workmentioning
confidence: 99%
“…A literature review has shown that many problems regarding ADL recognition were addressed, and the proposed solutions demonstrated good results [ 7 , 8 , 9 ]. However, the question remains what to infer from the recognized sequence of activities.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation